2016
DOI: 10.1097/scs.0000000000002947
|View full text |Cite
|
Sign up to set email alerts
|

Facial Artery Myomucosal Flap, Pedicled Solely on the Facial Artery

Abstract: Island FAMM flap, pedicled only on skeletonized facial artery, is not biologically accepted for clinical usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Massarelli et al [8] suggest that iFAMM ap pedicled solely on the facial artery with the surrounding fat tissue provides the correct venous drainage, without ap congestion. However, Rahpeyma et al [9] in experimental studies on dogs observed iFAMM ap loss in each case of facial vein ligation. For that reason, iFAMM ap, pedicled only on facial artery, is not acceptable for clinical usage [9].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Massarelli et al [8] suggest that iFAMM ap pedicled solely on the facial artery with the surrounding fat tissue provides the correct venous drainage, without ap congestion. However, Rahpeyma et al [9] in experimental studies on dogs observed iFAMM ap loss in each case of facial vein ligation. For that reason, iFAMM ap, pedicled only on facial artery, is not acceptable for clinical usage [9].…”
Section: Discussionmentioning
confidence: 92%
“…However, Rahpeyma et al [9] in experimental studies on dogs observed iFAMM ap loss in each case of facial vein ligation. For that reason, iFAMM ap, pedicled only on facial artery, is not acceptable for clinical usage [9]. In our case, the patient had facial vein and artery ligated during neck dissection 18 months earlier.…”
Section: Discussionmentioning
confidence: 92%
“…Massarelli et al [ 8 ] suggest that iFAMM flap pedicled solely on the facial artery with the surrounding fat tissue provides the correct venous drainage, without flap congestion. However, Rahpeyma et al [ 9 ] in experimental studies on dogs observed iFAMM flap loss in each case of facial vein ligation. For that reason, iFAMM flap, pedicled only on the facial artery, is not acceptable for clinical usage [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Rahpeyma et al [ 9 ] in experimental studies on dogs observed iFAMM flap loss in each case of facial vein ligation. For that reason, iFAMM flap, pedicled only on the facial artery, is not acceptable for clinical usage [ 9 ]. In our case, the patient had facial vein and artery ligated during neck dissection 18 months earlier.…”
Section: Discussionmentioning
confidence: 99%
“…This method is advantageous due to its accessibility, low harm to the donor site, and similarity to recipient tissue [ 32 ]. Rahpeyma et al showed that a superiorly based FAMM flap is a good option when the fistula in the palate is continuous with the alveolar cleft [ 33 ]. Furthermore, they explained that a musculomucosal flap of the facial artery that is only supported by the skeletonized artery alone, known as an island FAMM flap, is not considered viable for use in clinical settings due to biological factors [ 34 ].…”
Section: Reviewmentioning
confidence: 99%